2005
DOI: 10.1038/sj.ejcn.1602150
|View full text |Cite
|
Sign up to set email alerts
|

Lower resting metabolic rate and higher velocity of weight gain in a prospective study of stunted vs nonstunted girls living in the shantytowns of São Paulo, Brazil

Abstract: Objective: Previous studies have shown that stunting increases the risk of obesity in developing countries, particularly among girls and women, but the underlying reasons are not known. This study aimed to investigate the relationship between stunting, weight gain, and resting metabolic rate. Design and subjects: A prospective study was conducted over 36 months with girls from shantytowns in São Paulo, Brazil. A total of 15 stunted girls (S) were compared with 15 nonstunted (N) ones of similar weight for heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 27 publications
4
46
0
1
Order By: Relevance
“…In addition, we show that one-tenth of indigenous children are concurrently stunted and overweight or obese, which is directly tied to low levels of SES. Given the link between childhood stunting and the increased risk of chronic disease in adulthood (Sawaya et al, 2003), the combination of stunting and overweight in early childhood that we report here is likely to increase even further the health risks for these children in later life (Grillol et al, 2005). Overweight and obesity are now major public health concerns in Mexico, even among pre-school children from very low-income families living in rural areas.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, we show that one-tenth of indigenous children are concurrently stunted and overweight or obese, which is directly tied to low levels of SES. Given the link between childhood stunting and the increased risk of chronic disease in adulthood (Sawaya et al, 2003), the combination of stunting and overweight in early childhood that we report here is likely to increase even further the health risks for these children in later life (Grillol et al, 2005). Overweight and obesity are now major public health concerns in Mexico, even among pre-school children from very low-income families living in rural areas.…”
Section: Discussionmentioning
confidence: 71%
“…This tendency is referred to as 'metabolic adaptation' or 'poststarvation obesity' (40) . In a prospective study, Grillo et al (41) found that stunted children gained 6 kg/year while the non-stunted children maintained at 4 kg/year irrespective of both groups consuming similar diets. This was because during the follow-up period there was a lesser increase in RMR but a greater increase in the velocity of weight gain in the stunted group compared with the non-stunted group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, associations among women have only been observed in studies conducted in the developed regions of the country, suggesting that a minimum of food availability or the kind of food availability present in developed urban centres would be required for the expression of a possible metabolic programming at an early age (10) . In a recent study, a more accurate marker of early undernutrition -the ratio of height to sitting height -was also associated with a high percentage of fat and obesity in a survey of Brazilian women (11) .A possible physiological mechanism to explain these associations is low energy expenditure among women exposed to energy restriction during development, as shown for Brazilian adolescents with stunting (12,13) . A complementary rather than alternative hypothesis in explaining the effects of early undernutrition is that promotion of growth by increased postnatal nutrition increases later risk as observed in a randomised trial of CVD (14) .…”
mentioning
confidence: 89%